Disabilities and depression in young adolescents living in underdeveloped areas of Indonesia: results from the 2018 Indonesia Basic Health Survey - Christiana Rialine Titaley; Nailul Izza; Dwi Hapsari Tjandrarini; Hadi Ashar; Janti Pare Nari; Maxwell Landri Vers Malakauseya; Felly Philipus Senewe; Muhamad Arif Musoddaq; Nazarina Nazarina; Donny Kristanto Mulyantoro; Yurika Fauzia Wardhani (BMJ Open)
Objectives This study aimed to investigate the association between the type and severity of disabilities and depression among adolescents aged 15–17 years living in underdeveloped areas of Indonesia.Design Cross-sectional study.Setting Data were derived from the 2018 Indonesia Basic Health Research, a nationally representative data of Indonesia.Participant We used information collected from 4811 adolescents aged 15–17 living in underdeveloped areas of Indonesia.Primary outcome The primary outcome was depression, based on the conditions experienced by respondents during the last 2 weeks.Results The analysis showed that 5.65% of adolescents aged 15–17 years living in underdeveloped areas of Indonesia had depressive symptoms. Adolescents with severe physical and psychological disabilities were most at risk, exhibiting significantly higher odds of developing depression (aOR=12.09, 95% CI: 5.41 to 27.03, p<0.001). Other significant predictors included female adolescents (aOR=2.18, 95% CI: 1.51 to 3.14, p<0.001) and those who had a non-communicable disease (aOR=3.50, 95% CI: 1.00 to 12.18, p=0.049).Conclusions These findings highlight the critical need for targeted depression interventions and collaborative efforts to support vulnerable adolescents in underdeveloped areas of Indonesia, particularly those with disabilities, girls and those with non-communicable diseases. Efforts to engage healthcare providers, educators and policymakers to improve access to mental health resources will enhance the overall well-being of vulnerable populations.